Evolució de la sintaxi dels contextos de polaritat negativa en castellà i català - Camus Bergareche, Bruno (Caplletra. Revista Internacional de Filologia, 2007)
In this paper we would like to compare the evolution of the syntax of polar contexts in Catalan and Spanish. By doing so, it would be possible to explain the greater syntactic disponibility of Catalan quantifiers and the important constraints for the same class of words in Spanish.After presenting in the first section the main theoretical questions about polarity in natural languages, we will describe in the second section the syntax of corresponding contexts in Middle Ages for both languages. Then, in the third section we will attend to the evolution towards current situation in order to understand the nature of modern differences between Catalan and Spanish on this area of their syntax.